WOUND AND INJURY CARE TRAINING TO IMPROVE NURSE KNOWLEDGE AT THURSINA MEDICAL CENTRE - Efris Kartika Sari; Dina Dewi Sartika Lestari Ismail; Dewi Purnama Sari; Ahmad Hasyim Wibisono; Eka Nur Jannah; Bella Nove Khirria; Marisa Devina Agustin (Caring : Jurnal Pengabdian Masyarakat, 2022)
Injuries to school-age children can results in wound and tissue damage. Improper treatment of wound and injury has the potential to cause wider tissue damage. The community service program of wound and injury care training aimed to improve the knowledge and skills of nurses at Thursina Medical Centre about wound care and injury management based on the lastest evidence-based practice. The activties were conducted from September to December 2021 which comprises topics wound care, injury management, and acute wound care practice. The level of knowledge of nurses was identified through the research using a single group pretest-posttest design. The results demonstrated that the average scores of topics wound care and injury management were increased by 8.57 ± 10.59 points and 10 ± 18.52 points respectively, although statistical analysis showed that there was no significant difference in pretest and posttest scores (p<0.05). The level of knowledge of nurses about wound and injury care increased after the implementation of community service program at Thursina Medical Centre.